Oral administration of active vitamin D metabolites to low birthweight infants. Issue 8 (August 1986) - Kovar, I Z; Mayne, P D; James, J J; Barnes, I C
Abstract : The active vitamin D metabolites 1 alpha, 25-dihydroxycholecalciferol (Rocaltrol) and the analogue 1 alpha-hydroxycholecalciferol (One-Alpha) are adequately absorbed after oral administration in the preterm infant. The absorption pattern is similar to that seen in adults.